DNA Methylation: A Key Player in Ovarian Serous Adenocarcinoma: A Review - Imrana Tanvir; Amer Shafie; Abdel Rahman (Pakistan Journal of Medical & Health Sciences, 2024)
Ovarian cancer, particularly serous adenocarcinoma, in women, is the most significant cause of cancer-related death, with its progression strongly linked to epigenetic modifications, notably DNA methylation. Epigenetic biomarkers, especially changes in DNA methylation patterns, have significant prognostic value in cancer, aiding in risk assessment and the development of therapeutic strategies. Two major epigenetic alterations are commonly seen: global DNA hypomethylation, which can activate oncogenes, and CpG island hypermethylation, which silences tumour suppressor genes. Understanding these epigenetic mechanisms not only deepens knowledge of ovarian cancer’s molecular basis but also opens avenues for more accurate early detection, personalized treatment, and preventive measures. Keywords: DNA methylation, Serous adenocarcinoma, Ovarian cancer, Epigenetic, hypermethylation